Determination of ester position in isomeric (O‐acyl)‐hydroxy fatty acids by ion trap mass spectrometry. (25th September 2016) - Marshall, David L.; Saville, Jennifer T.; Maccarone, Alan T.; Ailuri, Ramesh; Kelso, Michael J.; Mitchell, Todd W.; Blanksby, Stephen J.
Abstract : Rationale: ( O ‐acyl)‐hydroxy fatty acids (OAHFAs) are a recently discovered class of endogenous lipids, generating significant interest for their correlation with enhanced glucose tolerance. Structural variants that differ in the position of the ester linkage have been described, including the ω‐OAHFA sub‐class, that plays a key role in stabilizing the human tear film. Developing analytical tools for rapid and unambiguous structural elucidation of OAHFAs is essential to understanding their diverse physiological functions. Methods: Commercially available and synthesized OAHFA standards were dissolved in chloroform and subsequently diluted into methanol with 1.5 mM ammonium acetate. Negative ion collision‐induced dissociation (CID) MS n spectra were acquired using chip‐based nano‐electrospray ionization (Advion TriVersa NanoMate) coupled to an Orbitrap Elite mass spectrometer (Thermo Fisher Scientific). Results: Major product ions observed during CID of [OAHFA – H] − ions readily identify the constituent fatty acid and hydroxy fatty acid; however, isomers are not easily distinguished. Interrogation of the hydroxy fatty acid and dehydrated hydroxy fatty acid product ions by MS n and ion‐molecule reactions yielded diagnostic ions that readily pinpoint hydroxylation position and, thus, the OAHFA ester location. Conversely, these ions are characteristically absent in the MS 3 spectra of ω‐OAHFAs. Unimolecular dissociation mechanisms are proposed, which are shown to be consistent with prior isotopic labelling experiments. Conclusions: A mechanistic rationale is provided to explain the unimolecular dissociation of [OAHFA – H] − ions in an ion trap mass spectrometer, thus enabling near‐complete de novo structural elucidation of OAHFAs in shotgun lipidomics workflows, even if synthetic standards are unavailable for comparison. Copyright © 2016 John Wiley & Sons, Ltd.